PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH DAN KUALITAS SUMBERDAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN GOWA - Ansir Launtu (AkMen JURNAL ILMIAH, 2021)
This study aims to test and analyze the effect of the application of the Regional Government Accounting System and the Quality of Human Resources on the Quality of the Financial Statements of the Gowa Regency Government. Collecting data using primary data obtained from questionnaires by using purposive sampling technique. The Populations are SKPD in Gowa Regency with a total of 52 SKPD, while the samples taken were 25 SKPD in the form of service and there were 72 respondents. The results of the questionnaire have been tested for validity and reliabilit, also has tested the assumptions of classical form of the assumptions of normality and multikolonieritas. Methods of data analysis using multiple regression techniques. The results showed that partially and simultaneously the application of the Regional Government Accounting System and the quality of human resources had a positive and significant effect on the quality of the financial statements of the Gowa Regency government.